"The churchwardens have not used to meddle with anie seate": seating plans and parochial resistance to Laudianism in 1630s Somerset. Issue 2 (15th March 2018) - Reeks, John
ABSTRACT: This article considers the impact of the Laudian Reformation upon the spatial organisation of early modern English parish churches, drawing upon the Somerset churchwardens' accounts and court depositions of the 1620s and 1630s. An explosion of scholarly literature on early modern church seating plans and pew disputes has increased our understanding of how early moderns used the parish floor space to represent and reinforce social hierarchies and relationships. This paper investigates the significance of pewing practices to understanding parochial receptions of Laudianism, which required an overhaul of church interiors and which impacted seating arrangements in turn. It proposes that Laudian attempts to enforce a radical restructuring of churches, and to co-opt the churchwardens in pursuit of their policies, ran against established and hotly defended practices for the organisation of the parochial space.